Competition and Commercial Media Bias - Andrea Blasco; Francesco Sobbrio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper reviews the empirical evidence on commercial media bias (i.e., advertisers influence over media accuracy) and then introduces a simple model to summarize the main elements of the theoretical literature. The analysis provides three main policy insights for media regulators: i) Media regulators should target their monitoring efforts towards news contents upon which advertisers are likely to share similar preferences; ii) In advertising industries characterized by high correlation in products' qualities, an increase in the degree of competition may translate into a lower accuracy of news reports; iii) A sufficiently high degree of competition in the market for news drives out commercial media bias.
Keywords: L13; L15; L82; D82; 330